2015
DOI: 10.1186/1471-2105-16-s18-s2
|View full text |Cite
|
Sign up to set email alerts
|

PCTFPeval: a web tool for benchmarking newly developed algorithms for predicting cooperative transcription factor pairs in yeast

Abstract: BackgroundComputational identification of cooperative transcription factor (TF) pairs helps understand the combinatorial regulation of gene expression in eukaryotic cells. Many advanced algorithms have been proposed to predict cooperative TF pairs in yeast. However, it is still difficult to conduct a comprehensive and objective performance comparison of different algorithms because of lacking sufficient performance indices and adequate overall performance scores. To solve this problem, in our previous study (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In MVIAeval, we implemented two existing comprehensive performance scores [48, 49] to provide the overall performance comparison results for the selected benchmark microarray datasets and performance indices. The first one, termed the overall ranking score (ORS), is defined as the sum of the rankings of an algorithm for the selected performance indices and benchmark microarray datasets [48, 49].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In MVIAeval, we implemented two existing comprehensive performance scores [48, 49] to provide the overall performance comparison results for the selected benchmark microarray datasets and performance indices. The first one, termed the overall ranking score (ORS), is defined as the sum of the rankings of an algorithm for the selected performance indices and benchmark microarray datasets [48, 49].…”
Section: Methodsmentioning
confidence: 99%
“…The first one, termed the overall ranking score (ORS), is defined as the sum of the rankings of an algorithm for the selected performance indices and benchmark microarray datasets [48, 49]. The ranking of an algorithm for a specific performance index and a specific benchmark microarray dataset is d if its performance ranks #d among all the compared algorithms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another several algorithms integrated more than two high-throughput data sources ( 19–23 ). Previous studies ( 24 , 25 ) have shown that the performance of an algorithm is varied under different evaluation criteria such as the existence of physical/genetic interaction and the overlap with the benchmark set of known cooperative TF pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the comprehensive transcription factor (TF)-gene binding data, TF-gene regulation data and mutant phenotype data are available in yeast, this gives us an opportunity to construct the transcriptional regulation association and the mutant phenotype association in yeast. Moreover, we have many experiences in developing databases and web tools [ 6 - 13 ].…”
Section: Introductionmentioning
confidence: 99%